A new solution for UHDP and UHDR (Flash) measurements: Theory and conceptual design of ALLS chamber. (October 2022) - Di Martino, Fabio; Del Sarto, Damiano; Giuseppina Bisogni, Maria; Capaccioli, Simone; Galante, Federica; Gasperini, Alessia; Linsalata, Stefania; Mariani, Giulia; Pacitti, Matteo; Paiar, Fabiola; Ursino, Stefano; Vanreusel, Verdi; et al.
Highlights: Ultra High dose- per -pulse regimes (UHDP) still pose serious challenges to dosimetry A theory has been developed for designing a new chamber (ALLS), using a noble gas at variable pressure ALLS protype has been designed for measuring dose- per -pulse up to 40 Gy within 1 % accuracy Abstract: Ultra-High dose- per -pulse regimens (UHDP), necessary to trigger the "FLASH" effect, still pose serious challenges to dosimetry. Dosimetry plays a crucial role, both to significantly improve the accuracy of the radiobiological experiments necessary to fully understand the mechanisms underlying the effect and its dependencies on the beam parameters, and to be able to translate such effect into clinical practice. The standard ionization chamber in UHDP region is significantly affected by the effects of the electric field generated by the enormous density of charges produced by the dose pulse. This work describes the theory and the conceptual design of a gas chamber (the ALLS chamber ) which overcomes the above-mentioned problems.